Is there a stratospheric pacemaker controlling the daily cycle of tropical rainfall?. Issue 4 (18th February 2017) - Sakazaki, T.; Hamilton, K.; Zhang, C.; Wang, Y.
Abstract: Rainfall in the tropics exhibits a large, 12 h Sun‐synchronous variation with coherent phase around the globe. A long‐standing, but unproved, hypothesis for this phenomenon is excitation by the prominent 12 h atmospheric tide, which itself is significantly forced remotely by solar heating of the stratospheric ozone layer. We investigated the relative roles of large‐scale tidal forcing and more local effects in accounting for the 12 h variation of tropical rainfall. A model of the atmosphere run with the diurnal cycle of solar heating artificially suppressed below the stratosphere still simulated a strong coherent 12 h rainfall variation (~50% of control run), demonstrating that stratospherically forced atmospheric tide propagates downward to the troposphere and contributes to the organization of large‐scale convection. The results have implications for theories of excitation of tropical atmospheric waves by moist convection, for the evaluation of climate models, and for explaining the recently discovered lunar tidal rainfall cycle. Key Points: Model experiments show that the diurnal cycle of solar ozone heating in the stratosphere by itself excites a large diurnal rainfall cycle Stratospheric heating forces a downward propagating tide which then interacts with tropospheric convection to produce a rainfall response Our results have implications for the recently discovered lunar tidal rainfall cycle and for the theory of excitation of tropical waves